Efficient Heuristic Based on Clustering Approach for OLSR - Ali Choukri; Ahmed Habbani; Mohamed El Koutbi (Journal of Computer Networks and Communications)
Due to the dynamic nature of mobile ad hoc network (MANET), the quality of service (QoS) requires several improvements. The present papercomeswithin the framework of research to optimize QoS in MANET. In this paper, we propose a novel version of OLSR based on the clustering approach which is inspired from Lin and Chu heuristic and adapted to beimplemented inOLSR. We studied its stability and we compared its performances to those of standard OLSR. The metrics we used in evaluating network performances were average end-to-end delay, control routing overhead, and packet delivery ratio. Experimental results show that our alternative significantly reduces the traffic reserved to monitoring the network, which positively influences other performances such as throughput, delay, and loss.